Sliding cable modeling: An attempt at a unified formulation. (January 2018) - Coulibaly, J.B.; Chanut, M.-A.; Lambert, S.; Nicot, F.
Abstract: Sliding cable structures are systems where cables experience a relative sliding motion with other structural elements. The variety of structural systems using sliding cables led to a great diversity and scattering of the modeling approaches. This paper presents original developments expanding and generalizing the existing works and proposes a multi-node sliding cable model accounting for friction, with a general dynamic formulation, an effective numerical implementation and applicability to various material behaviors. General sliding equations are formulated, along with the unstretched length conservation constraint. Closed-form expressions of the Newton–Raphson scheme are developed to solve the sliding equations analytically while enforcing the conservation constraint. The formulation and its implementation are validated against a theoretical dynamic sliding cable mechanism and simulation results agree perfectly with the analytical solutions. The model is used to perform a parametric study of a complex system of sliding cables under dynamic loading. These simulations highlight the influence of the investigated parameters and prove the robustness and versatility of the proposed model over the existing ones from the literature.